Determining effectiveness of asset size based peer groupings in financial ratio analysis of PSE-listed food and beverage manufacturers using both plain averages and weighted means for the years 2007 to 2010 - Delfino, Neriza M. (Animo Repository, 2011)
This study attempts to determine if a system of peer groupings amongst PSE-listed food and beverage manufacturers get to exhibit significant differences in the group’s financial performance by way of analysis and comparison of financial ratios among a widely used category of ratios falling under liquidity, efficiency, asset turnover and profitability. Results have been mixed when only averages of ratios were utilized. This only revealed a few relatively significant differences in means. However, when the ratios were weighted according to asset size, the results showed substantial and significant differences of means in all categories of rations, but more prominently in asset turnover and profitability. Grouped date, furthermore revealed valuable insights into the relationships between asset size and some of the more important ratios identified in literature. The year 2008 revealed some distinct difference in peer group financial performance using both averages and weighted means which could have been largely influenced by the onset of the global crisis, particularly among the bigger firms that have subsidiaries overseas or are exporters of manufactures goods.